O contexto histórico-social do trabalho dos sujeitos da Associação de Catadores de Materiais Recicláveis de Dois Vizinhos-PR. - Rocha, Daiane Cristina da (2020)
The present work highlight the historic and social route of the working relationship of Recyclable Materials Collectors’ (CMR), in constitution of the recycling experience with wastes and with the aspects work-related in CMR’s organization association. Its highlight the elements constituent of subject CMR’s work, from your toil, specific of work at Association Recyclable Materials Collectors’ of the Dois Vizinhos-PR (ACAT-DV). The development this case study was 13 interviewed, among them the associate participants, the chairman and the technician provided by Municipal Government to support ACATDV. The main objective was analyzing the historic-social elements of the work constitution, in the view of the CMR subjects, from the toil at ACAT-DV. The determinants factors this process takes place research of the historic-socioeconomic aspects and political, that its visibility to the CMR work, in identification in the historicsocial-context of ACAT-DV praxis, in meaning and perspective of the work in CMR life. The researches disclose the late recognition or inexistent of the recyclable materials collectors’ and the way as was imposed the aid laws and social responsibilities that in actions are strangers. The workers life’s unequal context, either in social context, in work or in education, limit and it conduct to the survival working. The ACAT-DV advances and declines derive from needs significant gains with the recyclable materials, so these are the main income source to payment of charges and attributes to workers. This reality disclose the collector adaptation to follow the conditions of recyclable market system, it’s greater in COVID-19 pandemic context, produces more with less and income reduction, so an essential socio-environmental work. The characteristics of activity are allied to the unequal context of opportunities, in formal education too. In these conditions, the educational question stay by any means unnecessary and the work come back increasingly primordial in this life condition. By the same token this labor appears rooted as a family activity that passes through generations that experience since the childhood. The ACATDV collector associate is subject’s fight, resistance and overcoming limits imposed from Association development, your life is work and by means of its know the elements of the social life, in unequal conditions considered as normal that it disclose as an educational principle too.